2020
DOI: 10.1111/ijcp.13591
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the studies that evaluate the performance of the DAPT score

Abstract: Background The Dual Antiplatelet Therapy (DAPT) score was derived to determine which patients may benefit from prolonged DAPT therapy after 12 months based on the balance between ischaemic and bleeding events. Several studies have attempted to validate the score with inconsistent findings. Methods We conducted a systematic review of the studies that evaluated the DAPT score in PCI populations. A search was performed on MEDLINE and EMBASE and two independent reviewers reviewed the search results for study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…The current focus on DAPT-scoring systems may eventually assist in this process. Still, in the short term, the proliferation in competing systems for risk definition and inconsistent outcomes has added a further complexity level [5,[9][10][11][12]. Considering that the risk of bleeding is higher and the risk of ischemic events is lower in Asians than in non-Asians [13,14], the balance between ischemic and bleeding events in Japan appears to be different from that in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The current focus on DAPT-scoring systems may eventually assist in this process. Still, in the short term, the proliferation in competing systems for risk definition and inconsistent outcomes has added a further complexity level [5,[9][10][11][12]. Considering that the risk of bleeding is higher and the risk of ischemic events is lower in Asians than in non-Asians [13,14], the balance between ischemic and bleeding events in Japan appears to be different from that in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction rule assigns 1 point each for myocardial infarction at presentation, prior myocardial infarction or PCI, diabetes, stent diameter less than 3 mm, smoking, and paclitaxel-eluting stent; 2 points each for history of congestive heart failure/Low ejection fraction and vein graft intervention; −1 point for age 65 to younger than 75 years; and −2 points for age 75 years or older[ 21 ]. The DAPT score has been validated in several studies outside its derivation cohort; however, these studies have yielded conflicting results in which some have confirmed its predictive value and some have not[ 22 ]. Of note, most of the analyses were from registries and a substantial number of patients were treated with bare-metal stents or first-generation DES.…”
Section: Resultsmentioning
confidence: 99%
“…In the PRECISE-DAPT score, eGFR < 30 mL/min by itself increases patients bleeding risk to the highest quartile, whereas milder CKD is associated with a slight to moderate risk. It must be noticed that in the DAPT score, CKD is not considered as a variable because the associated increased bleeding risk was balanced by an almost identical increased ischemic risk[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the benchmark, two validated scores (i.e., the DAPT score and the PRECISE-DAPT score) that are extensively applied in clinical studies (35, 36), served as the potential candidates. The PRECISE-DAPT focuses mainly on forecasting the out-of-hospital bleeding risk, while the DAPT score was dedicated to estimating the incidence probabilities of both events, which matches our prediction task.…”
Section: Methodsmentioning
confidence: 99%